COMMON MENTAL DISORDERS AND CIRCULATORY DISEASES ASSOCIATED PREVALENCE: AGE RELATED DIFFERENCES FROM A HEALTH SURVEY ANALYSIS : COMMON MENTAL DISORDERS AND CIRCULATORY DISEASES - Gianini, Reinaldo; Salvestro, Gabriel (British Journal of Healthcare and Medical Research, 2022)
Background: Epidemiological studies reveals that there is a progressive increasing in the incidence of Mental Disorders. Concomitantly, Circulatory Diseases (CD) are a major adult health problem worldwide being the leading causes of death. Aims: This study aims to evaluate aspects related to the prevalence and its association between Common Mental Disorders (CMD) and CD in different age groups. Methods: It has been evaluated data from the 2015 São Paulo City Health Survey, which have classified CMD patients employing the Self Report Questionnaire-20, and have collected information of referred CD. To analyze the association between CMD and CD, Pearson chi-square, Satterthwaite corrected tests, univariate and multivariate Poisson regression has used. Results: Among the elderly, there was a greater strength of association between CMD and all the CD studied: Hypertension, Angina, Acute Myocardial Infarction, Cardiac Arrhythmias and Stroke (all with p<0.01). The CD more strongly associated with CMD was Cardiac Arrhythmias (adjusted PR=2.84; 95%IC=1.75-3.52). For Angina, the CMD was considered important risk factor because their precocious association (PR=5.42 for 15-29 years of age). Conclusion: CMD and CD share biopsychosocial factors and result in higher expenses for the Health System and for those patients. The action of multidisciplinary teams, especially in the sphere of Primary Care, is essential to reduce damage and better meet the specific needs of CMD and CD patients, with special attention to young people with CMD as a risk factor for CD and to elderly people already affected by such association.